(untitled) (Research, Society and Development, 2022)
Complications of hematopoietic stem cell transplantation are due to the histocompatibility between recipient and donor, the most serious of which is graft-versus-host disease (GVHD), which can present in an acute form (aGVHD) or chronic form (cGVHD) with dermatological manifestations observed in both. The aim of this study was to describe the dermatological manifestations of GVHD in patients undergoing hematopoietic stem cell transplantation. This is a retrospective descriptive study, whose data source were the medical records of patients who underwent allogeneic hematopoietic stem cell transplantation between 2015 and 2020 in a High Complexity Oncology Care Center located in the city from Rio de Janeiro, Brazil. Simple statistical analyzes described the variables investigated. Of the 89 patients who developed GVHD, most developed aGVHD, 57 in the classic form and 14 in the late form. The mean time between transplantation and GVHD was 84.19 days, being 38.03 days for classic acute cases, 235.42 days for late acute cases and 146.08 days for chronic cases. In both aGVHD and cGVHD, the most frequent dermatological manifestations were erythema, macula, pruritus and desquamation, and the most frequent anatomical regions were the chest, face and upper limbs. The timely identification of the dermatological manifestations of GVHD in patients undergoing hematopoietic stem cell transplantation depends on a detailed anamnesis and a thorough physical examination.